Peningkatan Keterampilan Peternak Itik Melalui Pelatihan Manajemen Usaha Dan Pengolahan Hasil Ternak Di Kabupaten Sidrap - Kasim, Kasmiyati; Abdullah, Agustina; Nur, Aprisal; Mutmainnah, Mutmainnah; Wicaksono, Andi Dharmawan; Qinayah, Mirnatul; Utami, Sri Wira (Pakis Journal Institute, 2024)
The low income of duck farmers in Sidrap Regency is caused by a lack of knowledge about business management and limited types of products produced. This community service activity aims to improve the skills of farmers through business management counseling and livestock product processing training. The methods used are group counseling and direct practice training in making processed duck egg products, namely salted eggs with pandan flavor variants. The results show a significant increase in farmers' knowledge about good business management, strengthening duck farmer group institutions, digital marketing and duck egg processing techniques, namely salted duck eggs with pandan flavor variants. In addition, new processed products have emerged that are diversified and have added value. Thus, farmers become more independent, competitive, and able to increase family income. This activity makes a positive contribution to the development of the duck farming sector in Sidrap Regency.